An Analysis of Plastic Surgeons' Social Media Use and Perceptions. (21st August 2018) - Economides, James M; Fan, Kenneth L; Pittman, Troy A
Abstract: Background: Social media have become ubiquitous in society with an increasing number of active daily users across multiple platforms. Social media use has grown within the field of plastic surgery; many surgeons have created a professional account to gain exposure. Objectives: This study investigates the patterns of use and perceptions of social media in plastic surgery. Methods: A 16-item questionnaire was sent electronically to board-certified plastic surgeons to investigate professional social media use and perceptions. A literature review of all studies pertaining to social media and plastic surgery was also undertaken. Results: An online survey was sent to 6136 ASPS members with 454 responses (7.4%). Of the respondents, 61.9% reported having an active professional social media account. Respondents whose practice primarily consisted of aesthetic/cosmetic surgery were the most likely to have an active professional social media account (79.4%). Nonacademic surgeons were most likely to maintain an active professional social media account (71.9%) compared with university-affiliated community surgeons (41.4%) and academic surgeons (29.5%). Nonacademic surgeons were more likely to believe social media is positive for the field (48.9%) compared with the other 2 cohorts (27.6% and 35.1%, respectively). Academic surgeons are more likely to believe social media worsens the image of the field (49.3%) vs the other cohorts (35.4% and 37.2%). Conclusions: Professional social media use is rising within plastic surgery. However, a dichotomy exists in acceptance. Private practice, younger surgeons are more likely to view social media as an acceptable method of reaching patients.